Psychometrics of Art – Validation of RizbA, a Quantitative Rating Instrument for Pictorial Expression. Issue 2 (3rd April 2022) - Schoch, Kerstin; Ostermann, Thomas
ABSTRACT: Although art has been subject to psychological research for some time, the artwork itself received little attention in quantitative research. The rating instrument for two-dimensional pictorial works ( RizbA ) fills this gap by providing a tool for formal picture analysis. This study validates the questionnaire on 294 images created by 147 non-artists. In an online test–retest study the material was rated by 880 (T1) and 475 (T2) experts in visual art using RizbA . Statistical quality criteria, Principal component analysis (PCA) and indices of factor similarity were computed. The overall test's capacity of differentiation yields a partial eta-squared of .28 (T1) and .33 (T2). Test–retest reliability is .93. PCA reveals an eight-factors solution. Tucker's coefficients of congruence range between |0.82| and |1.00|. Intraclass correlation coefficients are .81 (T1) and .84 (T2). Results indicate generalizability to nonprofessional art. As the first reliable tool for picture analysis, RizbA allows a more detailed examination of art and its correlates.